A-6 Pediatric Cerebral Cavernous Malformation, Type 1 (CCM1): Cognitive and Psychosocial Functioning, The Role of Neuropsychology, and Emerging Clinical Care Guidelines. (17th August 2022) - Petranovich, Christine; Campbell, Richard; Gill, Darbi; Hart, Blaine; Morrison, Leslie; Wilson, Kevin
Abstract: Objective: CCM1 is a rare condition that confers risk for negative neurological sequelae, including hemorrhage, seizures, and chronic headache. This study examines cognitive and psychosocial functioning in pediatric patients with CCM1 and describes emerging clinical care guidelines. Method: Twenty-two children and adolescents with CCM-1 and 7 non-affected relatives participated in this cross-sectional pilot study. Cognitive testing and behavior and emotion questionnaires were completed. A subset of participants with CCM1 (n = 11) had repeat brain MRI (average 4.89 years between scans). Results: Patients with CCM1 and their non-affected relatives did not differ on the NIH Toolbox Fluid and Crystallized composites (p > 0.05). Processing speed also did not significantly differ, although both group means were below average normatively (NIH Toolbox Pattern Comparison T-score; CCM1 = 31.50 [12.02], non-affected relatives = 37.57 [14.58]). In the subgroup with repeat imaging, slower processing speed was associated with an increase in large lesions (p = 0.03) and with younger age at CCM1 diagnosis (p = 0.04). Self- and parent-reported internalizing problems and parent-reported externalizing problems did not differ between groups (p > 05). In the CCM1 group, patient-reported disengaged coping was associated with more internalizing problems (p = 0.03). Conclusions: Neuropsychological evaluation is an important component of long-term, multi-disciplinary care for pediatric patients with CCM1, particularly if lesions are progressive. The pilot sample was overall well-adjusted behaviorally and emotionally. The use of disengaged coping strategies was associated with more internalizing symptoms and coping may be a key modifiable risk factor in this population. Psychosocial monitoring may therefore be warranted.